2013
DOI: 10.5665/sleep.2968
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Eszopiclone on Sleep Spindles and Memory Consolidation in Schizophrenia: A Randomized Placebo-Controlled Trial

Abstract: Eszopiclone significantly increased sleep spindles, which correlated with overnight motor sequence task improvement. These findings provide partial support for the hypothesis that the spindle deficit in schizophrenia impairs sleep-dependent memory consolidation and may be ameliorated by eszopiclone. Larger samples may be needed to detect a significant effect on memory. Given the general role of sleep spindles in cognition, they offer a promising novel potential target for treating cognitive deficits in schizop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
72
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 47 publications
(71 reference statements)
11
72
1
Order By: Relevance
“…In addition, reduced spindle activity in those with schizophrenia was associated with cognitive deficits (Wamsley et al, 2012). Interestingly, the administration of eszopiclone during sleep significantly increased spindle generation in individuals with schizophrenia and the increases correlated with overnight motor sequence task improvement (Wamsley et al, 2013). Taken together, these results suggest that individual differences in the degree to which there is optimal functioning of the TC system may dictate and support normal intellectual abilities (for a review, see Fogel & Smith, 2011).…”
Section: Discussionmentioning
confidence: 73%
“…In addition, reduced spindle activity in those with schizophrenia was associated with cognitive deficits (Wamsley et al, 2012). Interestingly, the administration of eszopiclone during sleep significantly increased spindle generation in individuals with schizophrenia and the increases correlated with overnight motor sequence task improvement (Wamsley et al, 2013). Taken together, these results suggest that individual differences in the degree to which there is optimal functioning of the TC system may dictate and support normal intellectual abilities (for a review, see Fogel & Smith, 2011).…”
Section: Discussionmentioning
confidence: 73%
“…In a small preliminary study, eszopiclone, which acts on γ-aminobutyric acid (GABA)-ergic neurons in the TRN 73 , significantly increased spindles in schizophrenia but not sleep-dependent memory 30 . In another study that did not include PSG, longerterm administration of eszopiclone improved working memory in schizophrenia, but not symptoms 74 .…”
Section: Discussionmentioning
confidence: 99%
“…To investigate SW-spindle coordination, we analyzed polysomnography (PSG) data from a previously reported study of chronic medicated schizophrenia patients and demographically-matched healthy controls 10,30 . Using this dataset, we previously reported that in the context of normal sleep architecture and quality, patients showed significant reductions in N2 sleep spindle number and density, low sigma (12-13.5Hz) power and cortical spindle coherence.…”
Section: Introductionmentioning
confidence: 99%
“…Eszopiclone is known to increase the duration of stage 2 sleep and to act on GABA neurons in the thalamic reticular nucleus where spindles are generated. A small (n ¼ 21) randomized placebo controlled trial noted significantly increased sleep spindle number and density during stage 2 sleep following 2 nights of eszopiclone 3 mg compared to placebo which correlated with enhanced though nonsignificant overnight motor sequence task improvement (Wamsley et al 2013). Previous studies noted that triazolam led to overnight deterioration of motor sequence tasks, although spindles increased, and zolpidem did not differ from placebo in its effects on memory.…”
Section: Place In Therapymentioning
confidence: 99%